Long-term phenobarbital treatment is effective in working-age patients with epilepsy in rural Northeast China: a 10-year follow-up study - Li, Rongxin; Zhao, Danyang; Li, Nan; Lin, Weihong (Frontiers in Neurology, 2024)
Introduction: Effective management of epilepsy in working-age patients is essential to reduce the burden on individuals, families, and communities. This study aimed to assess the long-term efficacy of phenobarbital (PB) in working-age patients with epilepsy in rural Northeast China and identify the risk factors for seizures during treatment. Methods: Patients aged 18-65 years diagnosed with convulsive epilepsy in rural areas of Jilin Province between 2010 and 2024 were included, and demographic and clinical data were recorded. Seizure frequency, self-efficacy, adherence, and adverse events (AEs) were assessed monthly. Results: Of the 3,568 participants, 288 (8.1%) withdrew from the study and 159 (4.5%) died. During the first year of treatment, 75.2% of patients experienced a ≥50% reduction in seizure frequency compared with baseline (considered as treatment effectiveness); 53.7% of patients were seizure-free. By the tenth year, 97.7% of patients showed treatment effectiveness, and 89.6% were seizure-free. Self-efficacy was improved in 37.8% of patients in the first year and in 72% of patients by the tenth year. The independent risk factors for seizures during treatment were higher baseline seizure frequency (odds ratio [OR]=1.431, 95% confidence interval [CI]: 1.122-1.824), presence of multiple seizure types (OR=1.367, 95% CI: 1.023-1.826), and poor adherence (OR=14.806, 95% CI: 3.495-62.725), with significant differences observed in the first, third, and fifth years. The most commonly reported AEs were drowsiness (43.3%), dizziness (25.0%), and headaches (17.0%), most of which were mild and decreased over time. Age at enrollment was the only factor influencing withdrawal (hazard ratio=0.984, 95% CI: 0.973-0.996, p=0.010), with a substantial number of patients who withdrew (32.6%) relocating for work. Cardiovascular disease was the primary cause of death, and age at enrollment was the only risk factor (hazard ratio=1.026, 95% CI: 1.009-1.043, p=0.002). Discussion: Working-age adults with epilepsy demonstrated a favorable response and tolerability to PB monotherapy. Baseline seizure frequency, seizure type, and adherence consistently predicted prognosis throughout the treatment period. Withdrawal was mainly explained by work-related pressures in this age group. Therefore, it is essential to implement interventions that support patient adherence to therapy and maintain stable regimens.